The Effect of Extraction Method on Total Phenolic Content and Antioxidant Activity of Salam Leaves (Syzygium polyanthum) using DPPH (1,1-Diphenyl-2-Picrylhidrazil) - Sri Luliana; Hafrizal Riza; Eneng Neni Indriyani (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Extraction is an important step in separating bioactive compounds from the plant. The selection of extraction technique is also important in the standardization of herbal products, for if not observed it can remove the desired soluble constituents. One of Indonesia’s endemic plants which have been proven to have an antioxidant activity is Salam leaves (Syzygium polyanthum). This study aims to determine the effect of extraction method on total phenolic content and antioxidant activity of S. polyanthum leaves by counteracting free radicals mechanism using DPPH. The S. polyanthum leaves were extracted by maceration, soxletation, and infusa methods, and tested for the total phenolic content and the antioxidant activity. The results showed that the total phenolic content of each method extration is different. The total of the phenolic content extraction by maceration, soxhlet, and infusa method respectively were 338.62±21.3; 227.72±21.6; and 144.48±8.2 mgGAE/g. The best antioxidant activity was maceration method with IC50 17.53±0.11 µg/mL followed by soxhlet and infusa which were 18.73±0.31 and 40.26±0.18 µg/mL. The research conclusion is that the extraction method has an effect on the total phenol and antioxidant activity of S. polyanthum leaves.